Chemical Composition and Nutritional Categorization of Fish Meals Produced and Marketed in Senegal for Animal Feeding - Ayssiwede, S.B.; Mouanda, V.C.; Issa, Y.A.; Djettin, A.E.; Hane, M.B.; Missohou, A. (Pakistan Journal of Nutrition, 2016)
We assessed the chemical and nutritional compositions of 154 fish meal samples produced and marketed in Senegal. The fish meal samples (93 from 4 artisanal and 61 from 3 industrial units) were collected, stored and analyzed in the Laboratory of Nutrition and Animal Feeding (LANA) of EISMV-Dakar from September 2012 to July 2013. The results showed that the fish meals produced in Senegal were all fatty, regardless of whether they were artisanal or industrial. Overall, they showed significant variation (p<0.05) in the averages of all chemical constituents and energy contents. Artisanal fish meals were significantly richer in fat (12.4 vs. 10.4% DM), ash (40.4 vs. 24% DM) and minerals (Ca, P, Na and K) than were industrial fish meals, which showed significantly higher levels of dry matter (93.3 vs. 92.1%), crude protein (63.4 vs. 41% DM), gross energy (4567 vs. 3430 kcal/kg DM) and metabolizable energy (3203 vs. 2409 kcal/kg DM). With the exception of phosphorus and sodium, for which there was significant variation among artisanal companies, there were significant differences observed in the nutrient contents between artisanal and industrial units. Globally, fish meals of various levels of nutritional quality are produced and marketed in Senegal. Low-protein fish meals (types 40, 35) are the most commonly produced (36.4%), followed by medium-protein fish meals (33.1%) and then high-protein fish meals (30.5%). The medium-protein fish meals (CP types 55 to 45, with medium ash content) were produced by both artisanal and industrial companies (37.6 vs. 26.2% of the artisanal and industrial samples analyzed, respectively). High-protein fish meals (CP types 70 to 60, with low ash content) were produced mainly by industrial units (29.2 vs. 1.3%, or 73.8% of the industrial fish meal tested), whereas low-protein fish meals (CP types 40 to 35, with often high ash) were almost always produced by artisanal companies (35.4 vs. 0.0%, or 60.2% of the artisanal fish meal analyzed). Moreover, the increase in ash content was accompanied by decreases in the contents of crude protein and metabolizable energy.